2021
DOI: 10.1038/s41467-021-23120-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanosensing of cells in synthetic 3D matrix with controlled biophysical dynamics

Abstract: Abstract3D culture of cells in designer biomaterial matrices provides a biomimetic cellular microenvironment and can yield critical insights into cellular behaviours not available from conventional 2D cultures. Hydrogels with dynamic properties, achieved by incorporating either degradable structural components or reversible dynamic crosslinks, enable efficient cell adaptation of the matrix and support associated cellular functions. Herein we demonstrate that given similar equilibrium binding constants, hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 54 publications
1
112
0
Order By: Relevance
“…Accumulative evidences have shown that the harbored cells can in real time perceive and respond to the surrounding microenvironment changes induced by external stimuli in a spatial- and temporal-controlled manner. 35 39 By adjusting intracellular signaling events such as dynamical integrin clustering regulation, focal adhesion (FA) complex accumulation and activation, cytoskeleton rearrangement, environmental cues-responsive proteins (e.g., Yes-associated protein (YAP), transcriptional co-activator with a PDZ-binding motif (TAZ), catenin, etc.) activation, gene expression, etc., cells displayed different biological characteristics and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulative evidences have shown that the harbored cells can in real time perceive and respond to the surrounding microenvironment changes induced by external stimuli in a spatial- and temporal-controlled manner. 35 39 By adjusting intracellular signaling events such as dynamical integrin clustering regulation, focal adhesion (FA) complex accumulation and activation, cytoskeleton rearrangement, environmental cues-responsive proteins (e.g., Yes-associated protein (YAP), transcriptional co-activator with a PDZ-binding motif (TAZ), catenin, etc.) activation, gene expression, etc., cells displayed different biological characteristics and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, hydrogels with dynamic characteristics, which are accomplished either through the integration of degradable structural compounds or reversible dynamic cross-links, permit efficient accommodation of cells to the matrix and aid in the achievement of the connected cellular specific functions (B. Yang et al, 2021 ). Since, it is well known that cancer cells can alter their extracellular matrix environment by secreting of molecules ( Dhar et al, 2018 ; Kano, 2015 ), release of exosomes ( Hoshino et al, 2015 ), degrading ( Stephens et al, 2019 ), re-orientating (aligning) (B.…”
Section: Environmental Matrix Viscoelasticity Acts On Cellsmentioning
confidence: 99%
“…Hydrogels containing more crosslinks promote osteogenic differentiation of the encapsulated cells. Bian et al demonstrated better spreading and osteogenic differentiation of encapsulated cells in hydrogels with large dissociation rate constants than those of hydrogels with low dissociation rate constants, which was dependent on the concerted action of the cell adhesion structures containing β1 integrins ( Yang et al, 2021 ). This indicates that the biofunctionalization of hydrogels also crucial for realizing ECM mimetic effects.…”
Section: Dynamic Biomaterial-mediated Stem Cell Fate Modulationmentioning
confidence: 99%